EGCG alleviates PM2.5-induced lung injury via activation of PPAR-γ to suppress inflammation and oxidative stress - Liu, Kai; Wu, Dean; Li, Chunyan; Tang, Dongxia; Xu, Chuanwei; Li, Tongjing (Frontiers in Pharmacology, 2025)
Fine particulate matter (PM2.5), a prevalent air pollutant, induces pulmonary injury by triggering inflammatory responses and oxidative stress, leading to cellular damage and tissue disruption. Epigallocatechin gallate (EGCG), a natural polyphenol compound derived from plants and known for its anti-inflammatory and antioxidant properties, has not been thoroughly investigated regarding its protective role and underlying mechanisms against PM2.5 triggered lung injury. This study employed a murine model of lung injury triggered by PM2.5 and the BEAS-2B cells to evaluate the effects of EGCG. We measured the levels of inflammatory cytokines and oxidative stress markers, alongside examining the expression of peroxisome proliferator-activated receptor gamma (PPAR-γ) and its downstream effectors nuclear factor-kappa B (NF-κB) and heme oxygenase-1 (HO-1). PM2.5 exposure induced pathological alterations in mouse lung tissues, including inflammatory cell infiltration and alveolar wall thickening. Both in vivo and in vitro, PM2.5 elevated pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α), increased reactive oxygen species and malondialdehyde levels, and reduced the activity of antioxidant enzymes (catalase and superoxide dismutase). Furthermore, PM2.5 suppressed PPAR-γ expression, activated NF-κB signaling, and decreased HO-1 expression. Pretreatment with EGCG effectively upregulated PPAR-γ expression, subsequently inhibited NF-κB activation, and enhanced HO-1 activity, thereby attenuating inflammatory and oxidative stress responses. Critically, co-administration of the PPAR-γ antagonist T0070907 partially reversed the EGCG’s protective actions, as evidenced by the renewed escalation in cytokine production and oxidative damage. Our findings demonstrate that EGCG, a promising plant-derived bioactive compound, may ameliorate PM2.5 related lung injury by modulating PPAR-γ, which consequently mitigates inflammatory signaling and oxidative imbalance. This study elucidates a novel pharmacological mechanism by which EGCG ameliorates air pollution-induced lung injury.